Pelatihan Penulisan Press Release Untuk Pegawai Komisi Pemilihan Umum (KPU) Kota Bandung - Olih Solihin; Rina Sovianti; Zikri Fachrul Nurhadi (Universitas Garut, 2022)
Abstract The Regional General Election Commission (KPUD) of Bandung City always provides news releases to the mass media regarding the implementation of its work program. To make a news release requires expertise in making news press releases according to journalistic rules. The purpose of this community service is to provide news writing training to the public relations staff of the Bandung City Election Commission. This training method was carried out in the Bandung City KPUD meeting room, attended by 20 participants. The implementation of the training began with the provision of general material on public relations, the rules of writing press releases, straight news news, discussions, and exercises. The result of this community service activity is that the speaker explained the role of public relations, strightnews, the relationship between public relations and mass media. In the discussion session, the presenters asked the participants' understanding and expertise in making news releases, as well as the obstacles they faced. Most of the training participants claimed to have understood and had the ability to make news releases for the mass media, while a small portion admitted that they did not really understand. This press release writing training is expected to increase the participants' understanding and expertise in making news releases for the mass media. Â Keywords: Jurnalitic news; mass media; news; Press release. Â AbstrakKomisi Pemilihan Umum Dearah (KPUD) Kota Bandung selalu memberikan release berita kepada media massa berkenaan dengan pelaksanan program kerjanya. Untuk membuat release berita tersebut memerlukan keahlian dalam membuat press release berita sesuai kaidah jurnalistik. Tujuan pengadian masyarakat ini adalah untuk memberikan pelatihan menulis berita kepada staf Hubungan masyarakat KPUD Kota Bandung. Metode pelatihan ini dilaksanakan di ruang pertemuan KPUD Kota Bandung, diikuti 20 peserta. Pelaksanaan pelatihan dimulai dengan pemberian materi umum mengenai humas, kaidah penulisan press release, berita stright news, diskusi, dan latihan. Hasil kegiatan pengabdian kepada masyarakat ini adalah, pemateri memaparkan mengenai peran humas, strightnews, kaitan kerja humas dengan media massa. Pada sesi diskusi pemateri menanyakan pemahaman serta keahlian para peserta dalam membuat release berita, serta kendala yang dihadapinya. Sebagian besar peserta pelatihan mengaku sudah memahami dan memiliki kemampuan membuat release berita untuk media massa, sementara sebagian kecilnya mengaku belum terlalu memahami. Pelatihan menulis press release ini diharapkan akan meningkatkan pemahaman serta keahlian para peserta dalam membuat release berita untuk media massa.Kata-kata kunci: Berita; berita jurnalistik; media massa; press release.